Power integrity for nanoscale integrated systems - Hashimoto, Masanori; Nair, Raj (New York McGraw-Hill Education, 2014)
A comprehensive examination of the procedures necessary to mitigate the emission of noise in high-voltage circuitry design.
Includes bibliographical references and index.
Keywords: Integrated circuits; Signal integrity (Electronics); Power electronics